A Study on Awareness of Data Science and Artificial Intelligence Among College Students (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The present study investigates the awareness of Data Science and Artificial Intelligence among college students. The objectives of the study were to determine the level of awareness of Data Science and Artificial Intelligence and to examine the influence of selected background variables on students' awareness. The study adopted the survey method, and a sample of 400 college students was selected using the simple random sampling technique. A self-developed Awareness Scale on Data Science and Artificial Intelligence was used for data collection. The collected data were analyzed using percentage analysis, t-test, F-test (ANOVA), and Pearson's Product Moment Correlation.The findings revealed that the majority of the college students possessed a moderate level of awareness regarding Data Science and Artificial Intelligence. Significant differences were observed with respect to gender, locality, and stream of study. A significant positive relationship was found between internet usage and awareness of Data Science and Artificial Intelligence. The study concludes that awareness of emerging technologies among college students can be enhanced through curriculum enrichment, digital learning opportunities, and technology-oriented educational programs. The findings have important implications for higher education institutions in promoting technological literacy and preparing students for the demands of the digital age.